Histopathological features of juvenile-onset laryngeal papillomatosis related to severity - El Achkar, Vivian Narana Ribeiro [UNESP]; Duarte, Andressa; Carlos, Román; León, Jorge Esquiche; Ribeiro-Silva, Alfredo; Pignatari, Shirley Shizue Nagata; Kaminagakura, Estela [UNESP] (Wiley, 2019)
Background: Laryngeal papillomatosis (LP) is a disease that presents in both juvenile (JLP) and adult patients (ALP). This study correlated papillomatosis characteristics with the Derkay score. Methods: Retrospective data and biopsies of 36 patients with JLP and 56 with ALP were collected and separated into groups according to their scores. Results: The mean of the Derkay score, in the JLP group was 10.97 and in Group ALP was 8.26. The JLP group presented a more aggressive result than in the adult group (P =.02). In the JLP group, the respiratory difficulty (P =.01) and tracheostomy were correlated to a higher Derkay score (P <.05). Microscopically, the JLP samples presented a higher incidence of atypical mitosis and mitosis above the basal cells layer of the epithelium (P <.05) and these characteristics were correlated with a higher Derkay index (P =.03). Conclusion: Findings suggest that ALP and JLP can present different clinical courses and histopathological features. There was a higher degree of LP severity in JLP.
Keywords: epidemiology; histopathology; papilloma; Papillomaviridae